Prolonged starvation effects on ascorbic acid level in the muscles of a freshwater teleost, Clarias batrachus - Prasad, Nayan Kumar (Nepalese Journal of Biosciences, 2015)
The effect of prolonged food deprivation on ascorbic acid content of muscles has been observed in both the sexes of the fish. The level of ascorbic acid content was found relatively higher in males than in females. In males, the muscles showed higher value of ascorbic acid in normal condition (12.07mg/100gm) in comparison to that of females (9.66mg/100gm). During starvation, the gradual decrease in ascorbic acid level has been noticed in both the sexes of the fish. After 40 days of starvation, the higher depletion was observed in female (about 84%) and lower depletion in the male (about 81%) of C. batrachus. This shows substantial decline in aerobic and biosynthetic capacity of the fish during starvation period.